Factors Associated with Farmers’ Participation in the U.S. Conservation Reserve Program (CRP) - Suraj Upadhaya; Shreesha Pandeya; Lisa A. Schulte (Environmental Management, 2026)
The Conservation Reserve Program (CRP), the largest U.S. private lands conservation initiative, incentivizes farmers to retire environmentally sensitive land to reduce erosion, improve water quality, and enhance wildlife habitat. The program is currently under consideration for reauthorization by Congress. We assessed social, economic, and ecological factors associated with CRP enrollment to evaluate program effectiveness and guide future policy. Analysis of a 5-year (2015–2019) survey of Iowa farmers revealed several factors positively associated with participation. Most strongly, the farm-level ecological variable of the mean percent slope was positively associated with CRP adoption. A one-unit increase in mean percent slope increases the odds of enrollment by threefold. Farmers who received technical assistance from non-governmental agencies for the implementation of conservation practices, a social variable, were 88% more associated with enrollment in CRP. Cropland area, an economic variable, increased the odds of enrolling in CRP by 47%. Several additional variables were positively associated with CRP enrollment, including receipt of additional cost-share, attitudes toward nutrient management, involvement in watershed management groups, agronomic capacity, education, access to information from public sources, and age. The amount of land in pasture and the proportion of farmland rented were negatively associated with farmers’ CRP enrollment. Our findings highlight current program strengths that enhance conservation outcomes as well as potential future adjustments to further address cost and trust barriers.